Risk factors of ventilator-associated pneumonia in elderly patients receiving mechanical ventilation - Xu Y (Dove Medical Press, 2019)
Yue Xu,1 Chunyun Lai,2 Guogang Xu,3 Wenwen Meng,3 Jie Zhang,1 Huiru Hou,4,* Hongying Pi1,*1Department of Nursing, Chinese People’s Liberation Army (PLA) General Hospital, Chinese PLA Medical Academy, Beijing, People’s Republic of China; 2Department of Respiratory, The Second Medical Center & National Clinical Research Center for Geriatric Diseases, Chinese PLA General Hospital, Beijing, People’s Republic of China; 3The Second Medical Center & National Clinical Research Center for Geriatric Diseases, Chinese PLA General Hospital, Beijing, People’s Republic of China; 4Department of Nursing, The Second Medical Center & National Clinical Research Center for Geriatric Diseases, Chinese PLA General Hospital, Beijing, People’s Republic of China*These authors contributed equally to this work Purpose: The aim of this study was to verify the potential risk factors of ventilator-associated pneumonia (VAP) in elderly Chinese patients receiving mechanical ventilation (MV). The secondary aim of this study was to present logistical regression prediction models of VAP occurrence in elderly Chinese patients receiving MV.Methods: Patients (aged 80 years or above) receiving MV for ≥48 h were enrolled from the Chinese People’s Liberation Army (PLA) General Hospital from January 2011 to December 2015. A chi-squared test and Mann–Whitney U-test were used to compare the data between participants with VAP and without VAP. Univariate logistic regression models were performed to explore the relationship between risk factors and VAP.Results: A total of 901 patients were included in the study, of which 156 were diagnosed as VAP (17.3%). The incidence density of VAP was 4.25/1,000 ventilator days. Logistic regression analysis showed that the independent risk factors for elderly patients with VAP were COPD (OR =1.526, P <0.05), intensive care unit (ICU) admission (OR=1.947, P <0.01), the MV methods (P <0.023), the number of antibiotics administered (OR=4.947, P <0.01), the number of central venous catheters (OR=1.809, P <0.05), the duration of indwelling urinary catheter (OR=1.805, P <0.01) and the use of corticosteroids prior to MV (OR=1.618, P <0.05). Logistic regression prediction model of VAP occurrence in the Chinese elderly patients with mechanical ventilation:Logit (P) = (−6.468) + 0.423X1 + 0.666X2 + 0.871X3 + (−0.501)X5 + 0.122X6 + 0.593X7 + 0.590X8 + 1.599X9.Conclusion: VAP occurrence is associated with a variety of controllable factors including the MV methods and the number of antibiotics administered. A model was established to predict VAP occurrence so that high-risk patients could be identified as early as possible.Keywords: aged, 80 and over, pneumonia, ventilator-associated, risk factors, prediction model